PBG 6. Genetic diversity assessment of selected Philippine inbred rice (Oryza sativa L.) lines and its use in hybrid rice breeding (2018)
Identification of heterotic groups reduces the task of crossing several parental lines to develop high-yielding hybrids. This study aims to assess the genetic diversity of the Philippine germplasm to help progress hybrid rice breeding through the establishment heterotic groups. Ten inbred lines were assembled as representative of 182 elite rice inbred lines from the hybrid rice breeding work of PhilRice CES and PhilRice LB-UPLB for half diallele crossing. The genetic diversity of the sample population was assessed by measuring phenotypic traits followed by the evaluation of combining ability and heterosis. Heterotic groups were established using different schemes, namely F1 yield per se, heterosis, heterotic grouping based on GCA of multiple traits (HGCAMT), specific combining ability (SCA), and heterotic group’s specific and general combining ability (HSGCA). Among the different schemes, classification of inbred lines based on F1 yield per se and heterosis were the most efficient at 66.67% with two heterotic groups followed by the groupings based on SCA and HSGCA at 44.44%, and HGCAMT at 34.29%. Therefore, the two-heterotic-group model is the most efficient classification for the evaluated set of inbred lines. However, the precise assignment of inbred lines into heterotic groups remains a challenge since there is no strong correlation between genetic distance estimates and hybrid performance, ranging from -0.3336 to 0.4677. To address this, there is a need to diversify the Philippine germplasm to maximixe its genetic potential for hybrid breeding.